A Phase 2b randomized trial of lorecivivint, a novel intra-articular CLK2/DYRK1A inhibitor and Wnt pathway modulator for knee osteoarthritis. Issue 5 (May 2021) - Yazici, Y.; McAlindon, T.E.; Gibofsky, A.; Lane, N.E.; Lattermann, C.; Skrepnik, N.; Swearingen, C.J.; Simsek, I.; Ghandehari, H.; DiFrancesco, A.; Gibbs, J.; Tambiah, J.R.S.; et al.
Summary: Objective: Lorecivivint (LOR; SM04690), an investigational Wnt pathway modulator, previously demonstrated patient-reported and radiographic outcome improvements vs placebo in clinically relevant subjects with moderate to severe knee osteoarthritis (OA). This study's objective was to identify effective LOR doses. Design: Subjects in this 24-week, Phase 2b, multicenter, randomized, double-blind, placebo (PBO)-controlled trial received an intra-articular injection of 2 mL LOR (0.03, 0.07, 0.15, or 0.23 mg), PBO, or dry-needle sham. The primary efficacy endpoints were changes in Pain NRS [0–10], WOMAC Pain [0–100], WOMAC Function [0–100], and radiographic mJSW outcomes, which were measured using baseline-adjusted analysis of covariance at Week 24. Multiple Comparison Procedure-Modeling (MCP-Mod) was performed for dose modeling. Results: In total, 695/700 subjects were treated. Pain NRS showed significant improvements vs PBO after treatment with 0.07 mg and 0.23 mg LOR at Weeks 12 (−0.96, 95% CI [−1.54,  −0.37], P  = 0.001; −0.78 [−1.39,  −0.17], P  = 0.012) and 24 (−0.70 [-1.34,  −0.06], P  = 0.031; −0.82 [−1.51,  −0.12], P  = 0.022). Additionally, 0.07 mg LOR significantly improved WOMAC Pain and Function subscores vs PBO at Week 12 ( P  = 0.04, P  = 0.021), and 0.23 mg LOR significantly improved both WOMAC subscores at Week 24 ( P  = 0.031, P  = 0.017). No significant differences from PBO were observed for other doses. No radiographic progression was observed in any group at Week 24. MCP-Mod identified 0.07 mg LOR as the lowest effective dose. Conclusion: This 24-week Phase 2b trial demonstrated the efficacy of LOR on PROs in knee OA subjects. The optimal dose for future studies was identified as 0.07 mg LOR.